Abnormal movements are associated with poor psychosocial functioning in adolescents at high risk for psychosis - Mittal, Vijay A. (2011)
The period immediately preceding the onset of overt psychosis is characterized by a range of symptoms and behaviors including emerging attenuated psychosis, spontaneous movement abnormalities, and a broad decline in role and social functioning. Recent evidence suggests that basal ganglia dysfunction, which is implicated in the development of psychotic symptomatology, may manifest in the form of both movement abnormalities and deficits in processes integral to psychosocial functioning. However, little is known about the relationship between abnormal movement function and the observed psychosocial deficits. In the present study, 40 clinical high-risk participants meeting criteria for a prodromal syndrome were assessed for movement abnormalities and global role and social functioning at baseline. Role and social functioning was then followed up after a one-year period. At baseline, the severity of spontaneous movement abnormalities was associated with poor role functioning. Further, when controlling for baseline functioning, movement abnormalities predicted changes in social functioning one-year later, with a trend in the same direction for role functioning. Exploratory analyses also indicated that elevated baseline movement abnormalities distinguished those at-risk participants who eventually converted to psychosis and that this was also the case for poorer baseline global role functioning (at the trend level). Taken together, the results suggest that movement abnormalities are closely associated with deficits in psychosocial functioning. Elucidating the link between these phenomena may serve to refine etiological models of frontal-subcortical circuit dysfunction and inform understanding of functioning and outcome of these affected youth.